TRAINING OF INFORMATION TECHNOLOGY IN WEST JAVA SUMEDANG-REGIONAL LIBRARY AS AN EFFORT ON DIGITAL LITERACY EDUCATION - Komariah, Neneng; Saepudin, Encang (Record and Library Journal, 2019)
Background of the study: The Internet has become part of society's daily life. But the phenomenon shows that not all people are Able to use information technology and the Internet efficiently, and the information disseminated through the internet is not entirely quality information. Therefore, Internet users need digital literacy skills, that is the ability to use information technology efficiently and the ability to find, Evaluate, use, make information, and use it wisely, and lawfully. The problem is who should be held responsible to digital literacy education for the community. Public libraries can play a role in the digital literacy education for the community.Purpose: This study aims to find out how the management of ICT education in the Regional Public Library (PUSDA) of Sumedang Regency, West Java, as an effort for digital literacy education community.Method: The research method used is a qualitative method with descriptive analysis, and the data collection techniques with observation, interviews, focus group discussions, and literature study.Findings: The result shows the subject taught in ICT with the relevant training on participants' needs. The participants are students and jobless. Most of of participants did not have Reviews their own computer, they were very happy to take part in the ICT training in the library because it was free. Teachers are library staff and outside personnel assistance. Computer used are owned by the library and donations from industry. The way of teaching was easy to understand and the participants could practice using computers and search the internet. The PUSDA staff organized the training with enthusiasm.Conclusion: There are some aspects that are already owned by the public library which will support the implementation of digital literacy education effectively and efficiently. Among them is the library already has computer facilities, has a staff of professionals, and already has access to sources of digital information online